Filozofia polityczna Hansa-Hermanna Hoppego. Studium krytyczne - Slenzok, Norbert (1990- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present book offers a critical examination of the political philosophy of Hans-Hermann Hoppe, a leading libertarian thinker. In addition to expounding upon Hoppe`s philosophy, we also engage in assessing its truth value. This evaluation involves reinterpreting, reformulating, or even rejecting Hoppe`s arguments when necessary to refine and defend his overarching system. Indeed, it is exactly the book`s main thesis that Hoppean philosophy constitutes a full-fledged system. As is shown, that system springs up from epistemological rationalism (apriorism) conceived along the lines of Kantian transcendentalism and pragmatism, as reconstructed and integrated with one another by Karl-Otto Apel`s transcendental pragmatics of language, the Erlangen constructivist school, and Austrian school praxeology.
Keywords: libertarianizm; racjonalizm; teoria sprawiedliwości; prawo własności; anarchokapitalizm; libertarianism; rationalism; justice theory; property rights; liberty; anarcho-capitalism; Hoppe, Hans-Hermann (1949- ); filozofia niemiecka; filozofia polityczna; filozofia współczesna